Incidence and evolution of monoclonal gammopathy of undetermined significance (MGUS) in Greece - Anagnostopoulos, A.; Evangelopoulou, A.; Sotou, D.; Gika, D.; Mitsibounas, D.; Dimopoulos, M.-A. (Annals of Hematology, 2002)
Monoclonal gammopathy of undetermined significance (MGUS) is a relatively common condition among individuals older than 70 years. The actuarial risk of MGUS progression to an overt plasma cell malignancy (PCM) after 20 years of follow-up has been reported to be as high as 30%. The purpose of this study was to evaluate the incidence and evolution of MGUS in a Greek population: 1564 consecutive patients older than 50 years who were admitted to the Department of Clinical Therapeutics at the University of Athens School of Medicine for various reasons over a 26-month period were evaluated with serum protein electrophoresis. In cases in which a monoclonal protein was detected, a panel of tests was performed to rule out an underlying plasma cell malignancy (PCM). Serum levels of interleukin (IL)-6, IL-6-soluble receptor (IL-6SR), IL-1 beta, and transforming growth factor beta 1 were also measured in the MGUS cases. Patients with MGUS were monitored at regular intervals for evidence of multiple myeloma or other PCMs. The incidence of MGUS was 4% and there was a positive correlation with increasing age. The median value of serum M peak was only 5.3 g/l. After a median follow-up of 71 months, only two patients developed multiple myeloma (60 and 75 months after initial diagnosis). Our data are consistent with those of other epidemiological studies regarding the incidence of MGUS, but the monoclonal protein levels and the probability of evolution to a malignant plasma cell disorder appeared to be lower in our study than in other series. Our data support the hypothesis that individuals with low M peak values require only regular annual follow-up examinations.
Keywords: Greek population; Interleukin; MGUS; multiple myeloma; Transforming growth factor beta 1